Distributing foil from needle and syringe programmes (NSPs) to promote transitions from heroin injecting to chasing: An evaluation - Hunt Neil; Pizzey Rachael (BMC, 2008)
Abstract Background The report presents evaluation results from an intervention using specially produced foil packs to promote a transition from heroin injecting to inhalation (chasing) with injecting drug users (IDUs) attending four needle and syringe programmes (NSPs) in south west England. Methods Service activity/uptake measures, brief structured interviews. Results Out of 320 attenders, 54% took the foil packs when they became available. Over the period of the evaluation, NSP transactions increased by 32.5% from 1,672 to 2,216. Additionally, 32 new clients (non-injecting heroin users) started attending the service to obtain the foil packs. This group would not otherwise have been in contact with the treatment service. More detailed data from one site are reported for 48 recent injectors who took foil within the NSP where the piloting first commenced. Prior to the introduction of the foil packs, 46% of this sub-group reported chasing heroin in the previous four weeks. At follow up, 85% reported using the foil to chase heroin on occasions when they would otherwise have injected. Among the people who took it, client satisfaction with the quality and size of the foil packs was good and respondents viewed its availability as a valuable extension to the NSP's services. Conclusion These findings suggest that distributing foil packs can be a useful means of engaging NSP attenders in discussions about ways of reducing injecting risks and can reduce injecting in settings where there is a pre-existing culture of heroin chasing. Further research should see whether these findings can be reproduced in other cultural contexts and evaluate whether the observed behavioural changes are sustained and lead to reductions in harm including blood-borne infections and overdose.